Modified tarsorrhaphy versus gold weight implant technique for paralytic lagophthalmos treatment in patients with leprosy: One-year observation of a randomized controlled trial study - Irawati, Yunia; Natalia, Michelle Eva Rebeca; Gondhowiardjo, Tjahjono D.; Dachlan, Ishandono; Soebono, Hardyanto (Frontiers in Medicine, 2023)
Trial design This study was a multicenter, Prospective Randomized Open-label Blinded-Endpoint (PROBE) clinical trial, parallel-group study conducted in Indonesia (three sites). Methods The aim of this study was to compare the effectivity and efficiency of modified tarsorrhaphy (MT) and gold weight implant (GWI) techniques in the surgical treatment of paralytic lagophthalmos in patients with leprosy. The study sample consisted of 23 eyes, with 11 eyes in the MT group and the remaining 12 eyes in the GWI group—the control group. Results The central eyelid margin distance (lagophthalmos distance) decreased when gentle pressure was applied in the MT (3.09 mm to 0.43 mm) and GWI groups (3.21 mm to 0.83 mm) at postoperative year 1. The Ocular Surface Disease Index score, the tear break-up time, and the Schirmer test without and with anesthesia in the MT and GWI groups showed a p-value of > 0.05. Epitheliopathy improvement occurred in 54.55% of the MT group and 58.33% of the GWI group. Corneal sensitivity change in the inferior quadrant of the MT group (50.00 to 51.30 mm) and in the GWI group (49.61 to 52.93 mm) resulted in a p > 0.05. Postoperative complications occurred in 15% of patients in the GWI group. In addition, the surgery duration of both techniques was similar. Furthermore, the surgery cost in the MT and GWI groups yielded a p < 0.05. Conclusion The MT technique is as effective as the GWI technique but more efficient than the GWI technique as a surgical treatment for paralytic lagophthalmos in patients with leprosy. Clinical trial registration [www.ClinicalTrials.gov], identifier [NCT0494 4498].